Genome analysis of orf virus isolates from goats in the Fujian Province of southern China - Chi, Xuelin; Zeng, Xiancheng; Li, Wei; Hao, Wenbo; Li, Ming; Huang, Xiaohong; Huang, Yifan; Rock, Daniel L.; Luo, Shuhong; Wang, Shihua (Frontiers in Microbiology, 2015)
Orf virus (ORFV), a species of the genus Parapoxvirus of the family Poxviridae, causes nonsystemic, highly contagious and eruptive disease in sheep, goat, and other wild and domestic ruminants. Our previous work shows orf to be ubiquitous in the Fujian Province of China, a region where there is considerable heterogeneity among ORFVs. In this study, we sequenced full genomes of four Fujian goat ORFV strains (OV-GO, OV-YX, OV-NP and OV-SJ1). The four strains were 132 to 139 kb in length, with each containing 124 to 132 genes and about 64% G+C content. The most notable differences between the four strains were found near the genome termini. OV-NP lacked seven and OV-SJ1 lacked three genes near the right terminus when compared against other ORFVs. We also investigated the skin-virulence of the four Fujian ORFVs in goats. The ORFVs with gene deletions showed low virulence while the ORFVs without gene deletions showed high virulence in goats suggesting gene deletion possibly leads to attenuation of ORFVs. Gene 134 was disrupted in OV-NP genome due to the lack of initial code. The phylogenetic tree based on complete Parapoxviruse genomes showed that sheep originated and goat originated ORFVs formed distinctly separate branches with 100% bootstrap. Based on the single gene phylogenetic tree of 132 genes of ORFVs, 32 genes can be easily distinguished as having originated from sheep or goats. Multiple alignment of amino acid sequences of gene 008 from the genome of 5 goat ORFVs and 4 sheep ORFVs revealed 33 unique amino acids differentiating it as having sheep or goats as host. The availability of genomic sequences of four Fujian goat ORFVs aids in our understanding of the diversity of orf virus isolates in this region and can assist in distinguishing between orf strains that originate in sheep and goats.